Determinants of Passenger Satisfaction and Passenger Loyalty at Terminal 3 of Soekarno Hatta Airport - Cin Asmoro; Sarwono Hadi Saputro; Juliater Simarmata (Dinasti International Journal of Digital Business Management, 2024)
The article on the determinants of passenger satisfaction and passenger loyalty at Terminal 3 of Soekarno Hatta Airport is a scientific literature review article within the scope of marketing management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of marketing management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Service quality influences passenger satisfaction at Terminal 3 of Soekarno Hatta Airport; 2) The quality of information influences passenger satisfaction at Terminal 3 of Soekarno Hatta Airport; 3) Accessibility influences passenger satisfaction at Terminal 3 of Soekarno Hatta Airport; 4) Service quality influences passenger loyalty at Terminal 3 of Soekarno Hatta Airport; 5) The quality of information influences passenger loyalty at Terminal 3 of Soekarno Hatta Airport; 6) Accessibility influences passenger loyalty at Terminal 3 of Soekarno Hatta Airport; and 7) Passenger satisfaction influences passenger loyalty at Terminal 3 of Soekarno Hatta Airport.